IDentif.AI: Rapidly optimizing combination therapy design against severe Acute Respiratory Syndrome Coronavirus 2 (SARS-Cov-2) with digital drug development - Blasiak, Agata (Blackwell Publishing Ltd, 2022)
10.1002/btm2.10196